Analisis Peran Media Power Point dan Alat Peraga Periskop Untuk Meningkatkan Konsep Optik Siswa Kelas XI SMA Al-Furqon Jember - I Ketut Mahardika; Subiki Subiki; Alfiatun Hasanah; Cindy Ineke Ferdanti; Lisa Listyo Wati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Physics is an abstract subject. Some physics concepts are sometimes difficult to understand if only based on the explanation of the teacher's lecture. Therefore, we need a media to help make physics learning look more interesting and liked by students. Thus, the purpose of this study was to determine the role of power point and periscope props to improve the optical concept of class XI students at SMA Al-Furqon Jember. The research method used is quantitative research methods with data analysis techniques using descriptive techniques. The sample of this study was the 9th grade students of Al-Furqon High School Jember. The data collection technique used a survey method by giving a pre-test before applying the learning media and a post-test after applying the learning media to the students. The results of this study showed that the post-test scores of the students were higher than the pre-test scores. Thus, from this study it can be concluded that power point learning media and periscope teaching aids have proven to help improve the understanding of XI grade students at Al-Furqon High School regarding the concept of optical material.